Understanding Exercise Practices and Depression, Anxiety, and Stress in Senior Games Athletes: A Mixed-Methods Exploration. Issue 1 (January 2016) - Bardhoshi, Gerta; Jordre, Becca D.; Schweinle, William E.; Shervey, Sarah Wollersheim
Abstract : This mixed-methods study investigated depression, anxiety, and stress rates, measured by the Depression, Anxiety, and Stress Scale–21 (DASS-21), and exercise practices in a national sample of Senior Games Athletes (N = 383). Results demonstrated significantly lower DASS-21 scores for Senior Games Athletes compared with nonclinical normative data and no strong relationships between DASS-21 scores and demographic variables, exercise practices, and comorbidity. Senior Games Athletes reported high exercise volume and notably low comorbidity rates. Qualitative analysis of written responses revealed that participants related a healthy lifestyle with practicing healthy behaviors, experiencing optimal physical, emotional, and spiritual well-being, living life to the fullest, and social engagement.